1989
DOI: 10.1017/s0021859600084161
|View full text |Cite
|
Sign up to set email alerts
|

Some consequences of imposing different continuousgrazing pressures in the spring on tiller demography and leaf growth

Abstract: S U M M A R YThe effects of different severities of continuous grazing imposed during the spring, followed by a uniform continuous grazing management from mid-summer onwards, were examined in relation to changes in tiller demography and leaf growth of perennial ryegrass {Lolium perenne). Two grazing severities were imposed, based upon maintaining a constant sward height of either 35 mm (severe) or 75 mm (lenient). From 1 June onwards, a uniform grazing pressure with a sward height of 60 mm was imposed.Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1991
1991
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(14 reference statements)
0
3
0
2
Order By: Relevance
“…(Korte et al 1984;L'Huillier 1987b) have also reported insensitivity of reproductive development to differentgrazingmanagements. Even though low temperature followed by increasing photoperiod stimulates flowering (Jewis 1972), its timing can be altered by severe grazing during the previousseason (Tallowin et al 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Korte et al 1984;L'Huillier 1987b) have also reported insensitivity of reproductive development to differentgrazingmanagements. Even though low temperature followed by increasing photoperiod stimulates flowering (Jewis 1972), its timing can be altered by severe grazing during the previousseason (Tallowin et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive development in ryegrass affects the nutritive quality of pasture (Browse et al 1984;Tallowin et al 1989), and so spring management practices on some high-producing dairy farms (e.g., Davis et al 1979) are therefore aimed at maintaining the growth of vegetative tillers and minimising that of reproductive tillers. Allowing some reproductive tiller growth may be important, however, to promote survivalof daughter tillersformed followingflowering and persistence of ryegrass plants (Matthew et al 1989 a, b).…”
Section: Introductionmentioning
confidence: 99%
“…1983; Orr et al . 1988; Tallowin, Williams & Kirkham 1989). For example, continuous grazing by sheep of Lolium perenne L.‐dominated grassland can create tiller densities of 25–30 000 m −2 , almost twice those created under cutting at 4‐weekly intervals (Orr et al .…”
Section: Grassland Management Practices – Impacts On Plants Invertebmentioning
confidence: 99%
“…Nos capins Tanzânia e Mombaça, submetidos a pastejo rotacionado, a densidade populacional de perfilhos também foi maior no final da primavera (novembro/dezembro) e menor durante a fase reprodutiva (abril/maio), mantendo-se relativamente constante nos demais meses do ano (Santos, 1997 (Bircham & Hodgson, 1983;Grant et al, 1983). Tallowin et al (1989) determinaram que em áreas de azevém mantidas a 7,5 cm através de pastejo contínuo a produção de perfilhos era menor que em áreas a 3,5 cm, sendo este fato o principal responsável pela menor densidade populacional de perfilhos no tratamento mais alto.…”
Section: Perfilhamentounclassified
“…A área total destinada ao projeto foi de 6,3 ha, sendo 1,1 ha utilizados como "área de apoio" para a manutenção dos animais necessários ao ajuste de lotação, e 5,2 ha cultivados com (Bircham & Hodgson, 1983;Grant et al, 1983). Tallowin et al (1989) determinaram que em áreas de azevém mantidas a 7,5 cm de altura através de pastejo contínuo a produção de perfilhos era menor que em áreas a 3,5 cm, sendo este fato o principal responsável pela menor densidade populacional de perfilhos nas áreas pastejadas a 7,5 cm. Para o capim Tanzânia, Coelho et al (1999) (Barbosa et al 1998;Zimmer et al, 1999;Tamassia et al, 1999).…”
Section: Uso De Reserva De Nitrogêniounclassified